On one generalization of the Langevin equation with determinate modulus of velocity - Chalykh, E. V. (Ukrains’kyi Matematychnyi Zhurnal, 1998)
For a special class of systems of Itô stochastic equations with random coefficients, we establish conditions under which the modulus of the vector of state is not a random variable. We also consider possible ways of generalization of this problem.